Karakteristik makanan pendamping ASI balita yang disubstitusi dengan tepung ikan lele dan labu kuning - Noer, Etika Ratna; Rustanti, Ninik; Leiyla, Elvizahro (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2014)
Background: When breast milk is no longer enough to meet the nutritional needs of the infant, complementary foods should be added. Complementary feeding should be start giving from 6 months onwards. The period from 6-months of age is a very vulnerable period. It is the time when malnutrition starts in many infants. One form of complementary feeding which are hygienic, and ready to serve is an instant baby food. Utilization of local food such as catfish (Pangasius sp) and pumpkin (Cucurbita moschata) as a source of protein and beta-carotene may increase the nutrient content of complementary feeding. Objective: This study was designed to analyze the difference of nutrients content, bulk density, and acceptability among the percentage varieties of catfish and pumpkin flour substitution on instant baby porridge. Methods: An experimental study with a single factor completely randomized design. The experiment carried out by combining the percentage of catfish and pumpkin flour substitution in to 4 formulas. The nutrients content that were analyzed are levels of protein, betacarotene, fat, and carbohydrate. Statistical analysis of the nutrients content, bulk density, and acceptability using One Way ANOVA test CI 95% followed by Tukey posthoc test. Results: Instant baby food recommended is the substitution of catfish 20% and 15% pumpkin. Servings (25 g) instant baby food to meet the 34% and 102% of protein adequacy adequacy of vitamin A. Conclusion: Instant baby porridge substituted with catfish and pumpkin flour are high in protein and vitamin A, appropriate to the bulk density, and acceptable.